Peranan Workplace Well-Being Terhadap Turnover Intention Dengan Work Engagement Sebagai Mediator Pada Karyawan Generasi Milenial (Fakultas Ekonomi Universitas Gresik, 2023)
This research is motivated by the high level of job demands on PT X employees, affecting workplace well-being. There are several factors that have major influence on workplace well-being. However, this can be overcome with the job resources provided by the company. This study aims to see the role of job demands on workplace well-being with job resources as a moderator for PT X employees. The population in this study were all PT X employees and the sample used was 181 people. This study uses two measurements named The Job Demands-Resources Questionnaire by (Bakker, 2014) and The Workplace Well-being Questionnaire by (Parker & Hyett, 2011). The sampling technique used is convenience sampling. The data were processed using Moderated Regression Analysis (MRA) in the IBM SPSS version 20 program. The results showed that there was a positive role of job demands on workplace well-being for PT X employees with F = 56.101 and p = 0.000 <0.05. From the results of multiple linear regression analysis, the coefficient value RÃ‚Â² = 0.387 is obtained, the role of job demands on workplace well-being is 38.7%, while the remaining 61.3% is influenced by other factors. Other results show that job resources does not moderate the two variables in this study because the results obtained are p = 0.127 > 0.05